Informing the Physical Activity Evaluation Framework: A Scoping Review of Reviews. Issue 2 (February 2022) - Kosowan, Leanne; Shannon, Stephen; Rothney, Janet; Halas, Gayle; Enns, Jennifer; Holmqvist, Maxine; Wener, Pamela; Goertzen, Leah; Katz, Alan
Objective: Robust program evaluations can identify effective promotion strategies. This scoping review aimed to analyze review articles (including systematic reviews, meta-analysis, meta-synthesis, scoping review, narrative review, rapid review, critical review, and integrative reviews) to systematically map and describe physical activity program evaluations published between January 2014 and July 2020 to summarize key characteristics of the published literature and suggest opportunities to strengthen current evaluations. Data Source: We conducted a systematic search of the following databases: Medline, Scopus, Sportdiscus, Eric, PsycInfo, and CINAHL. Inclusion/Exclusion Criteria: Abstracts were screened for inclusion based on the following criteria: review article, English language, human subjects, primary prevention focus, physical activity evaluation, and evaluations conducted in North America. Extraction: Our initial search yielded 3193 articles; 211 review articles met the inclusion criteria. Synthesis: We describe review characteristics, evaluation measures, and "good practice characteristics" to inform evaluation strategies. Results: Many reviews (72%) did not assess or describe the use of an evaluation framework or theory in the primary articles that they reviewed. Among those that did, there was significant variability in terminology making comparisons difficult. Process indicators were more common than outcome indicators (63.5% vs 46.0%). There is a lack of attention to participant characteristics with 29.4% capturing participant characteristics such as race, income, and neighborhood. Negative consequences from program participation and program efficiency were infrequently considered (9.3% and 13.7%). Conclusion: Contextual factors, negative outcomes, the use of evaluation frameworks, and measures of program sustainability would strengthen evaluations and provide an evidence-base for physical activity programming, policy, and funding.